2008
DOI: 10.1037/0735-7044.122.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A role for dorsal and ventral hippocampus in inter-temporal choice cost-benefit decision making.

Abstract: Previous studies suggest a preferential role for dorsal hippocampus (dHPC) in spatial memory tasks, whereas ventral hippocampus (vHPC) has been implicated in aspects of fear and/or anxiety. In this study, we tested the hypothesis that vHPC may be a critical subregion for performance on a delay-based, cost-benefit decision making task. Rats chose between the two goal arms of a T maze, one containing an immediately available small reward, the other containing a larger reward that was only accessible after a dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 40 publications
9
51
2
Order By: Relevance
“…In three separate within-session delay discounting experiments, HPC lesions caused rats to decrease their choice of the large, delayed reward (Abela & Chudasama, 2013; Cheung & Cardinal, 2005; Mariano et al, 2009; McHugh, Campbell, Taylor, Rawlins, & Bannerman, 2008). Their increased discounting was not specific to either subregion, as lesions of both the dorsal and ventral HPC produced the same impairment (McHugh et al, 2008); nor could the effect be interpreted as stemming from deficits in magnitude or spatial discrimination or, by extension, memory (Mariano et al, 2009). A slightly different, yet complimentary effect was observed in the spatial adjusted delay task: even though HPC-lesioned animals were eventually able to titrate around a similar indifference delay as the controls; their training took much longer and their preference for the large reward was much more variable than controls (Bett, Murdoch, Wood, & Dudchenko, 2015).…”
Section: 0 Neural Basis Of Intertemporal Choicementioning
confidence: 99%
“…In three separate within-session delay discounting experiments, HPC lesions caused rats to decrease their choice of the large, delayed reward (Abela & Chudasama, 2013; Cheung & Cardinal, 2005; Mariano et al, 2009; McHugh, Campbell, Taylor, Rawlins, & Bannerman, 2008). Their increased discounting was not specific to either subregion, as lesions of both the dorsal and ventral HPC produced the same impairment (McHugh et al, 2008); nor could the effect be interpreted as stemming from deficits in magnitude or spatial discrimination or, by extension, memory (Mariano et al, 2009). A slightly different, yet complimentary effect was observed in the spatial adjusted delay task: even though HPC-lesioned animals were eventually able to titrate around a similar indifference delay as the controls; their training took much longer and their preference for the large reward was much more variable than controls (Bett, Murdoch, Wood, & Dudchenko, 2015).…”
Section: 0 Neural Basis Of Intertemporal Choicementioning
confidence: 99%
“…It has been shown that dorsal, ventral, and complete hippocampal lesions increase impulsive choice behaviour and lead to an increased preference for immediate low-reward options in contrast to delayed high-reward options in spatial (McHugh et al 2008) and non-spatial decision-making tasks (Mariano et al 2009). Since reward in the SRTT was given immediately after completing a FR13 run and animals could freely start the next run, an increased impulsive choice behaviour could have contributed to the observed shorter PRPs.…”
Section: Srttmentioning
confidence: 99%
“…It remains to be determined if this discrepancy is related to differences in training protocol (e.g., proportions of reinforced vs. non-reinforced trials) or the extent of lesion (20% vs. 35% of total hippocampal volume in the current and previous studies). An alternative interpretation of the lesion effect on timing accuracy is that DHPC lesions might have transiently induced impulsivity or a response inhibition deficit (Davidson and Jarrard 2004;Cheung and Cardinal 2005;McHugh et al 2008) rather than a temporal learning or memory deficit, leading to a leftward shift in central tendency in the first few blocks of the test phase. Indeed, the fact that the response distributions of the lesioned subjects were more dispersed than those of the sham animals is consistent with such a proposal.…”
Section: Acquisition Of Conditioned-response Timingmentioning
confidence: 99%